(untitled) (Zaporizhzhia Historical Review, 2021)
Lately it has begun to be noticed that not only are such particular items culture-specific but indeed the whole language is specific to the particular cultural surrounding. The translation became a transaction between two languages, but a more complex negotiation between two cultures. The unit of translation was no longer a word or a sentence or a paragraph or a page, but the whole language and culture in which the text was constituted.